AN ANALYSIS OF FITNESS BETWEEN A LESSON PLAN WITH SYLLABUS IN TERMS OF LEARNING OBJECTIVES, PROCEDURE, AND EVALUATION - Sri Meiweni Basra (Institut Pendidikan Indonesia Garut, 2022)
There are issues with teachers’ reluctance in writing their lesson plans. They use last year’s lesson plan, copy their friends’ lesson plan, or download it from the internet. The purpose of this study is to find out how lesson plans written by teachers teaching grade ten in a Senior High School in Bandung align with the syllabus in terms of learning objectives, procedure, and evaluation. The study applies the framework of descriptive study (qualitative research). One out of four lesson plans was chosen as the main object of the data which is analyzed using the adapted instrument from Evaluasi Diri Sekolah. The fitness among learning objectives, activities, and evaluation were analyzed in detail after checking out eight criteria of the interdependence of lesson plan and syllabus at a glance. The findings of the research described that the lesson plan analyzed aligns with the syllabus in terms of learning objectives, activities, and evaluation. The study concluded that a lesson plan should be developed by referring to the syllabus because the elements are interdependent. Hopefully, it is recommended for other teachers to develop their lesson plans by referring to the syllabus so that the alignment between the lesson plan and syllabus help in running a good teaching and learning process.